2004
DOI: 10.3171/ped.2004.101.2.0218
|View full text |Cite
|
Sign up to set email alerts
|

Frontoethmoidal encephalocele with ocular leakage of cerebrospinal fluid

Abstract: The authors present the case of a 2-year-old boy who was born with a small bulging mass in the middle frontonasal area and hypertelorism. In the neonatal period he suffered from a continuous lacrimal secretion mistaken for recurrent conjunctivitis. Cranial computerized tomography scanning and magnetic resonance imaging revealed a frontoethmoidal encephalocele associated with an ocular leakage of cerebrospinal fluid. One-stage repair of the encephalocele, along with correction of hypertelorism and bone grafting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Previous studies demonstrate that in patients with TB, decreased appetite leads to inadequate dietary intake, thereby reducing the intake of folic acid [8] . Folic acid has been shown to play an important role in the formation of the chondrocranium during the first week of pregnancy [9] . Micronutrients such as vitamins A, C, D, E, B6, and folic acid, the minerals zinc, copper, and selenium, and other dietary factors play an important role in metabolic processes and cellular and immune function [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that in patients with TB, decreased appetite leads to inadequate dietary intake, thereby reducing the intake of folic acid [8] . Folic acid has been shown to play an important role in the formation of the chondrocranium during the first week of pregnancy [9] . Micronutrients such as vitamins A, C, D, E, B6, and folic acid, the minerals zinc, copper, and selenium, and other dietary factors play an important role in metabolic processes and cellular and immune function [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Schütt et al [20] reported a case of fronto-ethmoidal encephalocele who had eyelid swelling and ocular leakage of CSF at presentation. It was hypothesized that there was a fistulous connection between the encephalocele and the lacrimal duct.…”
Section: Discussionmentioning
confidence: 99%